Methods for assessing the level of innovation of higher education institutions using integrated criteria - Lozova, T. (Економічний вісник Донбасу, 2024)
In the article methodological principles for assessing the level of innovation of higher education institutions using integral indexes are proposed, which characterize various aspects of the institution's internal potential and its use. The criteria for calculating the integral indicators of the level of innovation of HEIs and their purpose are determined. A methodology for the integral assessment of the level of innovation of HEIs is developed and a hierarchical scheme for calculating the combined integral index of innovation, which contains 13 blocks, is considered a typical form of monitoring and evaluating the activities of higher education institutions is proposed, on the basis of which it is possible to calculate integral indicators. It is proposed to consider the identification of the obtained results regarding the level of innovation of HEIs using the evaluation scale of the level of innovation, which has four classes. У статті запропоновано методичні засади оцінки рівня інноваційності закладів вищої освіти за допомогою інтегральних індексів, які характеризують різні аспекти внутрішнього потенціалу закладу та його використання. Визначено критерії щодо розрахунку інтегральних індикаторів рівня інноваційності ЗВО та їх призначення. Розроблено методику інтегральної оцінки рівня інноваційності ЗВО та розглянуто ієрархічну схему розрахунку зведеного інтегрального індексу інноваційності, яка містить 13 блоків. Запропоновано типову форму проведення моніторингу оцінки діяльності ЗВО, на основі якого можливо розрахувати інтегральні показники. Ідентифікацію отриманих результатів щодо рівня інноваційності ЗВО запропоновано розглядати за оціночною шкалою рівня інноваційності, яка нараховує чотири класи.